Reply letter to "safety of SARS-Cov-2 vaccines administration for adult patients with hereditary fructose intolerance". Issue 11 (2nd November 2021) - Saborido-Fiaño, Rebeca; Martinón-Torres, Nazareth; Crujeiras-Martinez, Vanesa; Couce, Maria Luz; Leis, Rosaura
ABSTRACT: In the letter, Urro et al. performed a search on the sucrose, fructose and sorbitol content in the approved Sars-Cov-2 vaccines and they concluded that these vaccines can be safely administered in adults affected by Hereditary fructose intolerance. The Pfizer-BioNTech COVID-19 Vaccine is currently approved for use in adolescents ≥ 12 years and the Moderna COVID-19 vaccine is close to approval for use in children over 12 years of age. Furthermore, both vaccines have initiated clinical trials that will include infant as young as 6 months. Therefore, we considerate important to analyze the safely administration of this two vaccines in children with Hereditary fructose intolerance.